Influence of neutralizing antibodies to adalimumab and infliximab on the treatment of psoriasis. (1st April 2014) - Bito, T.; Nishikawa, R.; Hatakeyama, M.; Kikusawa, A.; Kanki, H.; Nagai, H.; Sarayama, Y.; Ikeda, T.; Yoshizaki, H.; Seto, H.; Adachi, A.; Horikawa, T.; et al.
Summary: Background: Current treatment with biologics has produced dramatic therapeutic effects in patients with psoriasis, although these agents occasionally decrease in efficacy. One of the main factors responsible for this attenuation is attributed to the development of antidrug antibodies (ADAs). Objectives: To analyse the relationship between serum drug concentrations, the presence of ADAs and treatment efficacy of adalimumab and infliximab, and to determine the optimal use of these biologics. Methods: This was a 1‐year prospective study in the dermatology departments of Kobe University Hospital and collaborating hospitals. All patients starting a regimen of adalimumab and infliximab for psoriasis were included. We measured the serum concentration of the drugs and titres of antibodies to adalimumab and infliximab, as well as the Psoriasis Area and Severity Index scores at weeks 0, 4, 12, 24 and 48 during the first year of treatment. Results: We observed a 50% positive rate of ADAs to adalimumab, and a 41% positive rate of ADAs to infliximab. The titres of ADAs showed a wide range from low to high titres. In the high‐titre groups, the patients exhibited a decreased clinical response, and demonstrated a negative correlation between titre and clinical response. However, an equivalent therapeutic effect was observed between the low‐titre group and the group with no antibodies detected for adalimumab. For infliximab, the patients with ADAs showed decreased clinical response. An apparent negative correlation between antibody production and reduced clinical response was observed. Conclusions: Two biologics, adalimumab and infliximab, showed different therapeutic behaviour. The measurement of ADAs and drug concentrations has important implications for treatment with biologics.